Impact of body composition parameters on clinical outcomes in patients with metastatic castrate-resistant prostate cancer treated with docetaxel. (June 2016) - Cushen, Samantha J.; Power, Derek G.; Murphy, Kevin P.; McDermott, Ray; Griffin, Brendan T.; Lim, Marvin; Daly, Louise; MacEneaney, Peter; O' Sullivan, Kathleen; Prado, Carla M.; Ryan, Aoife M.
Summary: Background: Body composition may influence clinical outcomes of certain chemotherapeutic agents. We examined the prognostic significance of skeletal muscle mass and adipose tissue on docetaxel toxicity and overall survival in patients with metastatic castrate resistant prostate cancer (mCRPC). Methods: A retrospective review of patients medical records with mCRPC, treated with docetaxel was conducted. Body composition parameters (skeletal muscle mass, muscle attenuation [MA], visceral and subcutaneous adipose tissue) were measured at L3 by computed tomography (CT) and defined using previously established cut points. Toxicity profile was assessed after 3 cycles of the drug and graded according to the National Cancer Institute Common Toxicity Criteria (version 4). Overall survival was analysed. Results: Overall 63 patients, mean age 69 years (SD 8.3), were included. Sarcopenia was present in 47% (n = 30) and of these 26.7% (8/30) were sarcopenic obese. Common toxicities (all grades) observed included fatigue (80.9%), pain (46%), and constipation (34.9%). DLT occurred in 22 (34.9%) patients; of these 10 patients (15.8%) experienced dose reductions and 12 patients (19%) experienced dose terminations. Measurements of adiposity were not predictive of DLT, however 59.1% patients who had a combination of both sarcopenia and low MA experienced DLT compared to 29.3% of patients without sarcopenia and low MA (p = 0.021). Skeletal muscle index and MA were significantly lower in patients who experienced neutropenia (grade I–II) (46.5 cm 2 /m 2 vs. 51.2 cm 2 /m 2, p = 0.005) compared to their counterparts (24.6 HU vs. 32.2 HU, p = 0.044). Neither sarcopenia nor sarcopenic obesity was associated with overall survival. In multivariate analysis, BMI ≥25 kg/m 2 (HR: 0.349, CI: 0.156–0.782, p = 0.010) was a significant predictor of longer overall survival and both visceral fat index ≥ median 58.7 cm 2 /m 2 (HR: 2.266 CI: 1.066–4.814, p = 0.033) and anaemia (HR: 2.81, CI: 1.297–6.091, p = 0.009) were significant predictors of shorter overall survival. Conclusions: Sarcopenia and low MA are associated with neutropenia (grade I–II). Furthermore, presence of anaemia, high volume of visceral fat and BMI <25 kg/m 2 are associated with reduced survival in patients with castrate resistant prostate cancer being treated with docetaxel chemotherapy.